Northern Québec James Bay Cree Regional Health Governance in Support of Community Participation: Honouring the "Butterfly" - Lévesque, Martine C.; Law, Susan; Torrie, Jill; Carlin, Robert; Trapper, Lucy; Kutcher, Alison; Macdonald, Mary Ellen (International Indigenous Policy Journal, 2019)
Successful responses to the Truth and Reconciliation Commission of Canada's (TRC, 2015) Calls to Action require “joint leadership, trust-building, and transparency” between Canadian public institutions and First Nations. In the area of health and wellness, community participation in priority setting and planning constitutes one important step forward. In 2013, the Québec Cree regional health and social services agency launched a unique wellness planning initiative involving community participation in regional level policy-making. This article reports on a qualitative study conducted with key agency staff, an early component of a broader developmental participatory evaluation. Focusing on contextual challenges to and ways forward on community participation in planning, thematic analysis of 17 semi-structured interviews revealed important nuances between Cree and non-Cree perspectives: These perspectives reflected an empowerment versus a utilitarian view of participation, respectively. Cree Elders consulted on these results highlighted the ontological and epistemological distinction of Cree perspectives, and the importance of bringing these forth. These interpretations point to the relevance of extending cultural safety to institution-level processes bearing on relationships with communities and potentially building capacity for participation.